The 10 Largest Outpatient Disease Index Information System In Hospital X - Moh Rifky; Irda Sari; Falaah Abdussalaam (Institut Bakti Nusantara, 2022)
Disease index is an arrangement of summary lists, data on types of diseases and conditions of illness based on a classification system or numbering code as a means of communication. Good information can be displayed in a display, with that information will look more efficient and effective. One of the sheets contained in the Medical Record is the disease index. The method used is a qualitative research method with a descriptive approach, with data collection techniques based on observations, interviews, and literature studies. Problems found in this study: Data processing has not been carried out optimally so that officers take a long time, there is no special system for computerized disease indexes, disease index activity reports are still done manually. From the results of this study, Hospital X is expected to immediately make an outpatient disease module so that the physical activity proof of the Outpatient Disease Index display can be printed directly